2020
DOI: 10.1097/pas.0000000000001519
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiles of Mixed Endometrial Carcinoma

Abstract: Mixed endometrial carcinomas are defined as a combination of 2 or more distinct histologic subtypes, one of which must be a type II tumor comprising at least 5% of the tumor volume. The oncogenesis of these tumors remains unclear, particularly in light of the increasingly appreciated morphologic overlap among subtypes, as well as evolving molecular data. We evaluated 8 cases of mixed endometrial carcinoma, including 4 endometrioid (EC)/serous (SC), 1 SC/clear cell (CC), and 3 EC/CC cases, to study the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…The MEC rate was found to be 2.7% at the time of the study and it is compatible with the literature. The fact that the most common MECs are endometrioid and serous is consistent with the literature [9][10][11] . We demonstrated that there was no difference among the groups in terms of clinicalpathological features and prognosis.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The MEC rate was found to be 2.7% at the time of the study and it is compatible with the literature. The fact that the most common MECs are endometrioid and serous is consistent with the literature [9][10][11] . We demonstrated that there was no difference among the groups in terms of clinicalpathological features and prognosis.…”
Section: Discussionsupporting
confidence: 89%
“…They showed that different components had similar molecular features and they concluded that molecular analysis of mixed endometrial carcinomas revealed clonality in most cases. In another molecular study of 8 MEC cases demonstrated that targetable mutations might be existent in only one component of mixed tumors 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A point of concern may be the possibility of different TCGA signatures in the different components of a mixed carcinoma. Matrai et al reported the presence of POLE mutation limited to the SEC component of a mixed EEC/SEC [ 47 ]. In these cases, the prognosis might be driven by the component with the worse molecular signature.…”
Section: Mixed Carcinomamentioning
confidence: 99%